2006
DOI: 10.1590/s1516-89132006000100014
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive pattern comparison of Uca thayeri Rathbun, 1900 and U. uruguayensis Nobili, 1901 (Crustacea, Decapoda, Ocypodidae)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 16 publications
1
21
0
2
Order By: Relevance
“…Although the population studied in Samborombón Bay has a high density (César et al, 2005), the fact of having collected a low number of ovigerous females could be due to a differential behaviour during this incubation period. Costa et al (2006) captured the ovigerous females very deep in their burrows and suggested that this species would not feed during this period. On the other hand, U. uruguayensis presented continuous reproduction throughout the year in the north limit of its distribution (Brazil), while in the south (the population here studied in Samborombón Bay and the one studied by Spivak et al, 1991 Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the population studied in Samborombón Bay has a high density (César et al, 2005), the fact of having collected a low number of ovigerous females could be due to a differential behaviour during this incubation period. Costa et al (2006) captured the ovigerous females very deep in their burrows and suggested that this species would not feed during this period. On the other hand, U. uruguayensis presented continuous reproduction throughout the year in the north limit of its distribution (Brazil), while in the south (the population here studied in Samborombón Bay and the one studied by Spivak et al, 1991 Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the Uca species from intertidal brackish environments, such as U. triangularis (Milne-Edwards, 1873), U. annulipes (Milne-Edwards, 1837) and U. rapax (Smith, 1870), fecundity varied among 3390, 6400 and 28500 eggs/brood respectively, being their average sizes 9.6, 11.3 and 15.8 mm of carapace width (Thurman, 1985). On the other hand, the population of U.uruguayensis studied by Costa et al (2006) in Ubatuba, Brazil, presented a lower fecundity (mean fecundity: 1883 ± 490 eggs) than the population here studied, which is related to the smaller size in the ovigerous females captured (C.W = 6.6 ± 0.8 mm).…”
Section: Uca Uruguayensismentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few aspects of their population biology and the occurrence of parasites have been reported (Spivak et al, 1991;Costa et al, 2006). The present study compared SOM between two populations of U. uruguayensis from different geographical regions (Brazil and Argentina).…”
Section: Introductionmentioning
confidence: 88%